PENGARUH PENAMBAHAN SUSU SKIM SEBAGAI BAHAN PENGIKAT TERHADAP RASA DAN AROMA NUGGET AYAM - Faizin Marwanto; Supranoto; Fani Evadewi; Wida Nurnaningsih (Fakultas Peternakan. Unwiku, Purwokerto, 2024)
The research entitled The Effect of Adding Skim Milk as a Binder on the Taste and Aroma of Chicken Nuggets was conducted at the Laboratory of the Animal Husbandry Faculty of Wijayakusuma University in Purwokerto on May 28, 2024. The materials used in this study included 4000 grams of broiler chicken meat (breast part), 800 grams of wheat flour, 35 grams of ground pepper, 1440 grams of skim milk, 35 grams of salt, 8 eggs, 400 grams of ice, 1000 grams of breadcrumbs for coating, and 1 liter of cooking oil. The research method used was experimental with a Completely Randomized Design (CRD) in a single factor pattern. This study consisted of 4 treatments and 25 replications, with treatments including P0 (nugget batter without the addition of skim milk), P1 (addition of 5% skim milk by weight of the batter), P2 (addition of 10% skim milk by weight of the batter), and P3 (addition of 15% skim milk by weight of the batter). The observed variables were organoleptic tests of taste and aroma conducted by 25 semi-trained panelists. The data were analyzed using variance analysis followed by the Least Significant Difference (LSD) test. The results showed that the taste of chicken nuggets with the addition of skim milk had a very significant effect (P<0.01), and the aroma of chicken nuggets with the addition of skim milk also had a very significant effect (P<0.01). In conclusion, the addition of skim milk in the processing of chicken nuggets can enhance the flavor of chicken nuggets and is well accepted by the panelists